1995
DOI: 10.1111/j.1365-2842.1995.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Masseter muscle activity and the hypoglossal nerve

Abstract: The effects of severing the hypoglossal nerve and resultant restriction of tongue movement was evaluated for its effect on masticatory jaw movement. Electromyograms of masseter muscles in the feeding rat were recorded 3 days after the nerve severing operation at 1 week intervals. Even after severing the lateral branches of the hypoglossal nerve bilaterally, active-feeding behaviour continued with mastication slightly impaired. After severing the medical branches bilaterally, feeding behaviour was rarely observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…11 Further evidence of accommodation is the learned ability to avoid self-inflicted tongue trauma. Hara et al 12 investigated the impact of a transected hypoglossal nerve on jaw movement. They found only a slight impairment of mastication following bilateral severing of the hypoglossal lateral branches.…”
Section: Discussionmentioning
confidence: 99%
“…11 Further evidence of accommodation is the learned ability to avoid self-inflicted tongue trauma. Hara et al 12 investigated the impact of a transected hypoglossal nerve on jaw movement. They found only a slight impairment of mastication following bilateral severing of the hypoglossal lateral branches.…”
Section: Discussionmentioning
confidence: 99%
“…Contraction of the two extrinsic muscles, hyoglossus and styloglossus, retracts the tongue, while contraction of the inferior longitudinal muscle turns the tip of tongue downwards (2). A previous study recorded EMG activity from the masseter muscle during feeding in adult rats, which the medial branches of hypoglossal nerve (m‐XII) or the l‐XII were bilaterally severed (3). This study showed that the masseter EMG activity for 14 days after severing of the m‐XII was significantly smaller than that before the severing procedure, while the EMG activity preserved before and after severing of the l‐XII, suggesting that tongue movement controlled by the m‐XII plays an important role in performing masticatory movement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of these previous reports (3–5), few studies have evaluated specific functional roles of the XII in regulation of body weight and ingestive behaviours. In addition, no previous studies have qualitatively analysed changes in these three parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precise coordination of the jaw and tongue is essential for oral motor behaviors. It is well documented that tongue movement of mammals is coordinated intimately with jaw movement during dynamic functions in the oral facial region (Lowe, 1984;Dinardo and Travers, 1994;Hara et al, 1995). Although this physiological phenomenon was described by Schoen in 1931 as a jaw-tongue reflex (see Ishiwata et al, 2000) in the cat, the neuronal mechanisms that mediate jawtongue coordination have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%